Nursing Care For Patients Uterine Prolaps and Severe Anemia: Case Study - Chairunnisa, Kenny; Ermiati, Ermiati (Journal of Nursing Care, 2024)
Uterine prolapse is a condition where the uterus herniates into the vagina as a result of ligament failure and fascial support. Uterine prolapse often occurs together with prolapse of the vaginal wall, which involves the bladder or rectum. menopausal women. If uterine prolapse is not treated immediately, it can cause other health problems such as bleeding which can cause severe anemia. The purpose of this study was to describe nursing care that can be carried out in patients with uterine prolapse with severe anemia. The method used is a descriptive method with a case study approach, while the instrument used is an observation format at the Bandung City Hospital and an assessment format from the Unpad Faculty of Nursing. The sample in this study was one patient with uterine prolapse with severe anemia. The nursing diagnoses found in patients are the risk of shock, acute pain, and risk of infection. The implementation provided is in the form of shock management which includes blood transfusion therapy, tranexamic acid therapy, and monitoring of vital signs. Management of uterine prolapse in the form of Kegel exercises and placing a pessary, pain management, as well as prevention of infection. As a result, it was found that there was an improvement in the Hb value from 7 gr/dL to 10 gr/dL, complaints of weakness and pain decreased, and the patient had been placed with a pessary type pessary ring with support. The existence of uterine prolapse is necessary to increase awareness to prevent the incidence of uterine prolapse and to minimize the impact that occurs due to uterine prolapse, as well as to increase patient awareness to conduct examinations to health services.